Quality and Production Potentials of Various Types of Taro Cormel - Fauzan, Rafi; Widajati, Eny; Palupi, Endah Retno; Santosa, Edi (Department of Agronomy and Horticulture, IPB University, 2024)
Taro is a promising food crop that can be developed as a significant source of carbohydrates; however, a major obstacle is the unavailability of high-quality planting materials. Due to the difficulty in obtaining seeds, taro cultivation generally relies on vegetative propagation materials such as cormels, cormlets, and stolons. The advantage of using vegetative propagation material is that it retains the same characteristics as the parent plant. This research aimed to evaluate the quality of various types of cormels as taro planting material, study the potential of different types of cormels on the growth and production of taro plants, and investigate the growth, development, and time required to produce cormels from various types of cormels and their potential in cormel seed production. The research consisted of two experiments: the first experiment evaluated the quality of several types of cormels from two taro accessions (S24 and S28) using a completely randomized design with two factors (accession and types of cormels—primary, secondary, and tertiary), while the second experiment studied the growth and development of cormels from various types of cormels. The best quality seeds were obtained from primary cormels directly attached to the main tubers, with the germination rate highest for primary cormels at 53.25%, followed by secondary cormels at 51.59%, and tertiary cormels at 39.42%. Accession S24 showed a faster emergence rate (30.26 days) compared to S28 (58.08 days), and in S24, there was no significant difference between types of cormels for this parameter. In contrast, in S28, primary cormels had a significant emergence advantage (33.65 days) over secondary and tertiary cormels (62.57 and 78.02 days, respectively). Additionally, primary cormels were formed 8 weeks after planting, while secondary and tertiary cormels appeared 12 weeks after planting. These findings suggest that primary cormels should be prioritized for use in taro propagation to improve growth, development, and yield, highlighting their potential in cormel seed production and offering a viable solution to the challenge of seed availability in taro cultivation.